Freshwater structure and its seasonal variability off western Patagonia. (May 2019) - Saldías, Gonzalo S.; Sobarzo, Marcus; Quiñones, Renato
Highlights: The freshwater structure off western Patagonia is studied from Argo profiling floats. Satellite observations from Aquarius and SMAP show an extended low-salinity coastal region. The major content of freshwater is located off central Patagonia. Freshwater plays a minor role over stratification off northern and southern Patagonia. Abstract: Climatological hydrographic data for the southeastern Pacific from the World Ocean Atlas show an extended low-salinity region associated with high rainfall/river runoff along the Chilean Patagonia coast. However, the structure and variability of this extensive freshwater area is poorly understood due to the lack of periodic hydrographic observations. Here, we use 15 years of satellite observations in combination with hydrographic data from Argo profiling floats to increase our understanding of the freshwater structure and its seasonal variability off western Patagonia. Satellite-derived seasonal fields of surface salinity from Aquarius/SAC-D and SMAP (Soil Moisture Active Passive) satellite missions reveal a prominent coastal band of low-salinity water year-round (fresher during spring and summer). Hydrographic profiles from Argo floats confirm this coastal freshening. The major content of freshwater is located off central Patagonia, where the low-salinity surface layer dominates the stratification of the upper ocean. In contrast, the freshwater content plays a minor role in setting up the stratification off northern and southern Patagonia. A warm surface layer greatly increases the stability of the upper 500 m in the northern sector (especially in summer and fall), whereas cold temperatures in the southern region tend to damp zonal density gradients and decrease the stratification. Future studies at interannual scales are suggested considering the melting of Patagonian icefields since the 1960s.